Performance Improvement of KCS (Kalina Cycle System) 34 by Replacing Throttle Valve With Single-Screw Expander - Zhang, Xinxin; Li, Zhenlei; Wang, Jingfu; Wu, Yuting; Ma, Chongfang (Frontiers in Energy Research, 2021)
In order to recover the energy loss due to the throttling in the path of ammonia-lean solution in the Kalina Cycle System (KCS)34, two redesigned cycles, in which single-screw expanders that can perform two-phase expansion are used to replace the throttle valve, are proposed in this paper. The results show that the thermal efficiency and net work of two redesigned cycles are higher than those of the original KCS 34. With the concentration increase of ammonia-water mixture, the work produced by the single-screw expander B in two redesigned cycles gradually decreases, and the difference between the work produced in two redesigned cycles also gradually decreases. The original KCS 34 and two redesigned cycles have high exergy efficiency. The highest cycle exergy efficiency of 56.59% can be obtained in the II-redesigned cycle when the evaporation pressure is 3.0MPa and ammonia-water concentration is 0.75.